Biased self‐perceived social competence and engagement in subtypes of aggression: Examination of peer rejection, social dominance goals, and sex of the child as moderators. Issue 5 (2nd February 2016) - McQuade, Julia D.; Breaux, Rosanna P.; Gómez, Angelina F.; Zakarian, Rebecca J.; Weatherly, Julia
Abstract : This study expands on prior research suggesting that children who either over‐ or under‐estimate their social competence relative to others' reports are more likely to be aggressive. Linear and curvilinear associations between biased social self‐perceptions and forms (physical vs. relational) and functions (proactive vs. reactive) of aggression were tested along with three moderators (peer rejection, social dominance goals, and child sex). Children in the fifth through eight grade ( N = 167) completed self‐reports of perceived social competence and social dominance goals. Teachers completed ratings of children's social competence, peer rejection, and reactive and proactive physical and relational aggression. Bias in self‐perceived social competence was quantified as the residual difference between child and teacher ratings of the child's social competence. There was a significant interaction between quadratic bias and peer rejection predicting reactive physical aggression; rejected children with a positive bias or a negative bias were highest in reactive physical aggression. The interaction between linear bias, social dominance goals, and the sex of the child was also significant when predicting proactive physical aggression. Among girls who highly valued social dominance, a positive bias predicted greater proactive physical aggression. Results are discussed in terms of implications for aggression theory and intervention. Aggr. Behav. 42:498–509, 2016. © 2016 Wiley Periodicals, Inc.